The Relevance of Legal Protection to Human Rights Related to Euthanasia Law in Indonesia - Kadir, Yusrianto; Nurmala, Leni Dwi; Ismail, Nurwita (Universitas Negeri Gorontalo, 2021)
Every human being has rights that have been given since humans are in and the right to life is an absolute right that must be lived by every human being. Law Number 39 of 1999 concerning Human Rights does not provide space for euthanasia because euthanasia is contrary to the provisions of the Human Rights Law, especially the right to life of a person. The right to life in Law Number 39 of 1999 concerning Human Rights explains that every human being or every person without exception has the right to life, the right not to be tortured, the right to personal freedom thought and conscience, the right to religion, the right not to be enslaved, the right to recognized as a person and equality before the law, and the right not to study based on applicable law is a human right that cannot be reduced under any circumstances and by anyone.